Effect of different levels of chicken manure and ammonium phosphate on milkfish (Chanos chanos Forsskal) production in brackishwater ponds - Bara, Agabus
This study was conducted at the university of the Philippines in the Visayas, Brackishwater Aquaculture Center (UPV_BAC) Leganes, Iloilo from June 20 to November 30, 1983. Fifteen rectangular experimental ponds were used to determine the effect of different levels of chicken manure and ammonium phosphate (16-20-0) on milkfish production, gross primary productivity and some selected soil and water properties in a completely randomized design with three replications. The highest net fish yield of 502.12 kg/ha was obtained in Treatment III (1000 kg/ha chicken manure plus 50 kg/ha basal 16-20-0). This was followed by Treatment II (2000kg/ha chiken manure plus 50 kg/ha bas-1 16-20-0) with a net fish yield of 494.09 kg/ha. In Treatment V (no chicken manure but 75 75 kg/ha basal 16-20-0) the net fish yield (238 kg/ha) was lowest. Generally, treatments with chicken manure application (III, II, and I) had higher mean net fish yield than without chicken manure application (IV and V). Fish survival obtained in all treatments was low and ranged from 64.4% to 76.7%. However, the difference in mean percent survival among treatments were not significant. The highest gross primary productivity was recorded in Treatment I (21.27 ppm-0â‚‚). Generally, primary productivity increased after fertilizer application. Correlation analysis between gross primary productivity and fish yield showed high positive correlation. based on the results of this study the economic analysis showed that Treatment III (1000 kg/ha chicken manure, 50 kg/ha of ammonium phosphate in basal and 30 kg/ha in subsequent application is the most profitable. This treatment gave a net profit of â‚±2, 194.25 /ha per crop with a cost-benefit ratio of 1.43.